Analisa Rugi-Rugi Daya Feeder Lobak Pada Jaringan PT. PLN(Persero) Area Pekanbaru - Mardhatillah, M Faridh; Ervianto, Edy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The Imbalance loads of distribution channel in a power system will contribute to the presence of conductive permanent resistance. Good conductor should not have resistance, but in the reality every object has a resistance to electricity. Therefore it is necessary to do the calculation of the power losses generated by the conductor. In this research power loss calculations use approach method made on the primary distribution system by collecting data from PT.PLN to calculation of power losses absorbed or and generated, namely when the system load. Total power loss that has generated in this study are at 57346,4192 Watt and the percentage of power loss to the average load is equal to 1,047%. When compared with the approach method by Ardi on Feeder Adi Sucipto obtained the result of different amount of power loss because each feeder has different loadKeyword : Loss of power, The Imbalance Load, the primary distribution system